Fault Location with Load Profile Based Variation Compensation - ORPILLA, MICHAEL; GALLANO, RUSSEL JOHN; ORILLAZA, JORDAN REL (Philippine Engineering Journal; Vol 42 No 1 (2021), 2021)
Accurate and fast location of the fault is essential in distribution system operation to ensure continuity and quality of power supply. Many impedance-based fault location (IBFL) techniques such as Equivalent Impedance Based (EIB) and Load Level Based (LLB) perform load variation compensation but assume a uniform percent load change across all connected loads; such assumptions are hardly applicable in distribution systems where various types of loads are connected. It was observed in this study that their accuracy reduces as the fault current becomes comparable to the load current. This research performs load variation compensation by considering the load profiles of the various types of loads connected in the distribution system. By doing this, loads are better represented in the simulation, which results in better prediction accuracy. The proposed method, Load Profile Based (LPB), is compared to EIB and LLB in simulations conducted in an actual distribution feeder from Cagayan II Electric Cooperative. The results show improved fault location having an average relative error based on line length (RELL) at a high-impedance-fault scenario (Zf=100 ohms) not exceeding 3.22% compared to 48.74% (LLB) and 14.19% (EIB). In these techniques, a phasor measurement unit (PMU) is assumed to provide reference phasor voltage and currents at the root node. We further illustrate that additional PMU improves fault location by improving load variation compensation and faster fault location as PMU provides boundaries and effectively reduces the search space. Keywords — Fault Location, Load Profile Based, Load Variation Compensation, PMU